2022
DOI: 10.3389/fpsyg.2021.798090
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory and Its Mediating Role on the Relationship of Math Anxiety and Math Performance: A Meta-Analysis

Abstract: It is well established that math anxiety has a negative relationship with math performance (MP). A few theories have provided explanations for this relationship. One of them, the Attentional Control Theory (ACT), suggests that anxiety can negatively impact the attentional control system and increase one's attention to threat-related stimuli. Within the ACT framework, the math anxiety (MA)—working memory (WM) relationship is argued to be critical for math performance. The present meta-analyses provides insights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 111 publications
1
7
0
Order By: Relevance
“…In addition to the abundant literature showing the negative relationship between MA and WM, 5,33 there is also empirical evidence for a mediating role of WM capacity in the relationship between MA and math performance, [34][35][36][37][38][39][40][41] which was confirmed in a meta-analysis by Caviola et al, 5 albeit with very modest estimates in terms of magnitude (but see also Ref. 42 for an example of the absence of mediation).…”
Section: Executive Functions and Mamentioning
confidence: 82%
See 2 more Smart Citations
“…In addition to the abundant literature showing the negative relationship between MA and WM, 5,33 there is also empirical evidence for a mediating role of WM capacity in the relationship between MA and math performance, [34][35][36][37][38][39][40][41] which was confirmed in a meta-analysis by Caviola et al, 5 albeit with very modest estimates in terms of magnitude (but see also Ref. 42 for an example of the absence of mediation).…”
Section: Executive Functions and Mamentioning
confidence: 82%
“…This result is consistent with previous research specifically focused on this EF 64,65 and is also consistent more broadly with studies using WM tasks involving a continuous requirement to update information (see Refs. 5 and 33 for reviews). Neither switching nor inhibition were related to MA, which is in line with some studies using inhibition tasks 58,60 but not with other research reporting such a relation with inhibition 55,69 or switching tasks 50,52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of the present study was to extend the ACT framework to study the neurobiological associations between STEM-related anxiety and cognitive performance. Although the ACT framework has primarily been applied to the study of generalized anxiety, a recent meta-analysis demonstrated that math anxiety negatively impacts attentional control (Finell et al, 2022), confirming the relevance of ACT for STEM-related anxiety. Towards this end, we investigated STEM anxiety among undergraduate students enrolled in an introductory physics course.…”
Section: Introductionmentioning
confidence: 94%
“…Research has reported a range of moderators, such as gender, grade level, geographical region, and measurement, which influence the relationship between math anxiety and math performance (for a meta-analysis see Zhang et al, 2019 ). One of the most investigated moderator is cognitive processing, such that math anxiety negatively impacts working memory, which is in turn, critical for math performance (for a meta-analysis, see Finell et al, 2022 ). However, the causal direction of the negative relationship between math anxiety and math performance is highly debatable ( Carey et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%